READING HABITS TO IMPROVING STUDENTS’ VOCABULARY MASTERY (Karya Ilmiah Mahasiswa (KIMA), 2026)
The objectives of this research are to investigate how reading habit affects vocabulary mastery among the seventh-semester students of English Education at UMI,and to explore the correlation between reading habit and vocabulary mastery among the seventh-semester students of English Education at UMI. The researcher used a quantitative research and collected data by giving questionnaire and vocabulary test. There were 10 students of UMI in the Seventh semester involved in this study research. The results showed that the reading habits was significant in improving students'vocabulary mastery. This is because before using the readibg habits, the average score of students was 52.79, but after students used the Reading habits, the average score of students increased to 67.5 with a percentage increase of 27.86%. This significant increase occurred because the Reading Habits can help improve students' vocabulary mastery. Based on the result above, it can be seen that there is an improvement in students of UMI especially in Vocabulary mastery.